Progesterone-based estrous synchronization protocols in non-suckled and suckled primiparous Bos indicus beef cows - Sa Filho, O. G. [UNESP]; Dias, C. C. [UNESP]; Lamb, G. C.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2010)
In Experiment 1, effects of an intravaginal progesterone insert (CIDR) for synchronization of estrus in non-suckled cycling primiparous Bos indicus beef cows were evaluated. Cows received either no treatment (Control), prostaglandin F(2 alpha) (PGF), or CIDR (6 d)+prostaglandin F(2 alpha) (CIDR+PGF). There were greater (P<0.05) percentages of cows inseminated and pregnant in 4 d of breeding season in CIDR+PGF (81.6%; 48.7%) than in PGF (53.8%; 32.5%) and Control cows (14.6%; 8.5%). In Experiment 2, efficacy of a treatment with CIDR (6 d)+prostaglandin F(2 alpha)+48 h temporary weaning (CIDR+PGF+TW) associated or not with equine chorionic gonadotropin (eCG) for synchronization of estrus in suckled primiparous B. indicus beef cows was evaluated. Cows were assigned to receive either no treatment (Control), CIDR+PGF+TW, CIDR+PGF+TW+200 IU of eCG, or CIDR+PGF+IW+400 IU of eCG. There were greater (P<0.05) percentages of insemination and pregnancy in 4 d of breeding season in treatment groups (47.0%; 27.5%) than in Control cows(4.5%; 3.0%) and in cows treated with eCG (50.9%; 29.4%) than in cows treated only with CIDR+PGF+TW (39.4%: 23.7%). No effects of eCG dosage were detected. The percentage of cows inseminated and pregnant in a 30 d breeding season were greater (P<0.05) in cows assigned to synchronization treatments (53.3%; 37.2%) than in Control cows (35.3%; 21.4%). In the beginning of the BS, non-suckled primiparous cows treated with CIDR+PGF with estrous cycles having been initiated following calving had greater estrous detection and pregnancy rates than PGF and Control cows, and suckled primiparous cows had improved estrous detection and pregnancy rates when eCG was associated with CIDR+PGF+TW. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bos indicus; Estrus; Progesterone; Synchronization; eCG